Correlated complex independent particle potential for calculating electronic resonances - Sajeev, Y; Santra, R; Pal, S (Journal of Chemical Physics, 2005)
We have formulated and applied an analytic continuation method for the recently formulated correlated independent particle potential [A. Beste and R. J. Bartlett J. Chem. Phys. 120, 8395 (2004)] derived from Fock space multireference coupled cluster theory. The technique developed is an advanced ab initio tool for calculating the properties of resonances in the low-energy electron-molecule collision problem. The proposed method quantitatively describes elastic electron-molecule scattering below the first electronically inelastic threshold. A complex absorbing potential is utilized to define the analytic continuation for the potential. A separate treatment of electron correlation and relaxation effects for the projectile-target system and the analytic continuation using the complex absorbing potential is possible, when an approximated form of the correlated complex independent particle potential is used. The method, which is referred to as complex absorbing potential-based correlated independent particle (CAP-CIP), is tested by application to the well-known (2)Pi(g) shape resonance of e-N-2 and the B-2(2g) shape resonance of e-C2H4 (ethylene) with highly satisfactory results. (c) 2005 American Institute of Physics.